A study of critical success factors in system implementations. - Tan, Si Cheong. (2008)
This Final Year Project attempts to identify the critical success factors that contribute to system implementation success in our local context from the perspective of the users involved. We have classified the factors found in existing literature - according to the groups of people who have participated in the system implementation - into three major categories, namely information systems (IS) professionals, user and management.